Pinch-Exergy Approach to Enhance Sulphitation Process Efficiency in Sugar Manufacturing - Riadi, Indra; Sitompul, Johnner; Lee, Hyung Woo (Universitas PGRI Madiun, 2024)
This study aimed to enhance the thermal efficiency of the sulphitation process in the boiling house of sugar plants using a combined approach of pinch and exergy analyses. Pinch analysis is a reliable method for optimizing the design of energy recovery systems. However, the primary limitations arise from its exclusive focus on heat transfer processes. On the other hand, exergy balance provides valuable insight into the consumption of supplied exergy by individual process units, serving as a quantitative measure of inefficiency. The boiling house was evaluated and modified using pinch-exergy analysis with Sulphitation Process capacity production of 8000 TCD. The results showed a potential reduction in exergy destruction by approximately 10.25 MW. The optimization effort led to reductions of 18.18 and 14.70% in the use of hot and cold external utility, respectively.